The Impact of Value Chains on Food Security - Elena G. Kazantseva; Igor I. Lyamkin (Техника и технология пищевых производств, 2022)
Value chains are conduits that play an important role in global food security. The purpose of the study was to analyze the increasing impact of global value chains on national food security and develop proposals for improving the level of food security in Russia. The research featured the impact of value chains on food security. The study was based on a systematic analysis of data obtained from national statistical services, information and rating agencies, international organizations, etc. The impact of value chains on food security proved to be complex. On the one hand, they combine disparate links into a single system and allow for the rapid delivery of food to the end consumer. On the other hand, they increase the monopolization of the control links. The article introduces key features of the transformation of food value chains in recent decades. First, the list of participants often changes due to the growing contradictions between different countries and unpredictable foreign policy. Second, processing, logistics, and trade chains often get monopolized. Third, companies from other industries enter value chains from outside. Fourth, the distribution of income among chain participants becomes more uneven. Fifth, the influence methods of control links get more elaborate, etc. In general, companies tend to globalize their value chains while national governments strive to keep the chains within the country. The results of the study can improve value chains and food security in the country, while taking into account the interests of both chain participants and society, as well as the principles of sustainable development.